(untitled) (Journal Of Educational and Psychological Researches, 2022)
The current research aims to answer the following questions: what is the substance of democracy? What is the content of a democratic society? What is the role of university professor in the democratic development of the student university in light of the new Iraqi society? In order to achieve the goals of the research, the researcher developed an a questionnaire based on literature, Iraq’s draft constitution in 2005, and his experience of the field of teaching human rights and public freedoms and the teaching of democracy. It was applied to a sample of faculty members in Department of Education and Psychology / College of Education / University Baghdad for the year 20014 were obtained their answers were then processed statistically. Hence, the researcher reached to a number of conclusions and recommendations.